2016
DOI: 10.1186/s12913-016-1296-7
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in utilization of maternal and child health services in Ethiopia: the role of primary health care

Abstract: BackgroundHealth systems aim to narrow inequality in access to health care across socioeconomic groups and area of residency. However, in low-income countries, studies are lacking that systematically monitor and evaluate health programs with regard to their effect on specific inequalities. We aimed to measure changes in inequality in access to maternal and child health (MCH) interventions and the effect of Primary Health Care (PHC) facilities expansion on the inequality in access to care in Ethiopia.MethodsThe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 21 publications
(20 reference statements)
11
71
1
Order By: Relevance
“…Despite the binary nature of the dependent variables, a linear probability model is used. Available literatures suggest decomposition of C shows no significant differences whenever linear and non-linear models are used [30, 31]. …”
Section: Methodsmentioning
confidence: 99%
“…Despite the binary nature of the dependent variables, a linear probability model is used. Available literatures suggest decomposition of C shows no significant differences whenever linear and non-linear models are used [30, 31]. …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Memirie et al . () observed persistent wealth‐related inequality in Ethiopia. Utilization of primary care facilities for selected maternal and child health interventions showed pro‐poor improvement over the period 2005–11.…”
Section: Empirical Literaturementioning
confidence: 98%
“…Studies have reported demand and supply-side barriers to accessing and utilizing facility-based interventions. Demand-side determinants of access and use of MCH services in different LMICs are reported to be in uenced by individual, household, community and other contextual factors; with a variation across and within cultures [7][8][9][10]. Supply-side factors are attributed to inadequate number of health workers, reduced capacity and poor motivation of available staff , as well as other factors affecting their retention [6,11].…”
Section: Introductionmentioning
confidence: 99%